A Roadmap for Using Continuous Integration Environments. - Yu, Liang; Alégroth, Emil; Chatzipetrou, Panagiota; Gorschek, Tony (Communications of the ACM, 2024)
This research article investigates how continuous integration (CI) environments are utilized to evaluate quality attributes in industry, using Qvantel Sweden, Ericsson, Fortnox, and Company Alpha as the case companies. Research topics include a look at the existing CI environment in each company, how the CI environment is applied for quality attribute evaluation, challenges with the current processes and tools for evaluation, and how CI environments can evolve to meet the needs of the company.